Frequency jammer device / Nik Farahaida Nik Budiman …[et al.] - Nik Budiman, Nik Farahaida; Zainal Abidin, Nuradlin; Mazlan, Muhamad Mazwan; Azmi, Farid Hazwan (2019)
The frequency jammer device is our product that being innovated from situations when the students always play hand phone in class and also the private data always be shared from parliament to outsiders. Our company decide to make changes towards this current product because customers especially lectures, officers and parliament's staff give the feedback about the hard to handle their student or staff from access the internet or network data to play the social media websites. From here, we can assume that the most lectures and staff can gain the attention of their students or staffs. Besides, the parliament staff also can avoid their private data from can be separate. The unique part about our product is the holder range of frequency will be cut off. The feature can ease the student or staff to make a call or send the message to the outsiders and at the same time and receive the call or message so, in case the emergency happen, they can avoid the bad thing happen due to no service. We aim ro make the users or buyers comfortable, and the device is high quality and user friendly product to achieve our customer satisfaction.